Development of a Circular Motion Concept Inventory for Use in Ugandan Science Education - Kirya, Kent Robert; Mashood, Kalarattu Kandiyi; Yadav, Lakhan Lal (Journal of Turkish Science Education, 2024)
In this study, we administered and evaluated circular motion concept question items with a view to developing an inventory suitable for the Ugandan context. Before administering the circular concept items, six physics experts and ten undergraduate physics students carried out the face and content validation. One hundred eighteen undergraduate students responded to the 42 circular motion concept items. The data were analysed using the classical test theory (CTT) and item response curve (IRC) analyses. We calculated the difficulty level and index of discrimination and gauged the distraction efficiency of items. The IRCs revealed insights that were not evident from those provided by the CTT. Based on the IRCs, the circular concept items are classified into three categories: efficient, moderately efficient, and inefficient. This helped us better evaluate the quality of the items and their appropriateness for the population under consideration. We ended up with 22 circular motion concept question items which we call the circular motion concept inventory (CMCI). This inventory is particularly relevant to Ugandan context and may be useful to other countries in the East African region which share similar syllabi.